Involvement of Silicon Influx Transporter OsNIP2;1 in Selenite Uptake in Rice - Zhao, Xue Qiang; Mitani, Namiki; Yamaji, Naoki; Shen, Ren Fang; Ma, Jian Feng (Plant physiology (Bethesda), 2010)
Rice (Oryza sativa) as a staple food, provides a major source of dietary selenium (Se) for humans, which essentially requires Se, however, the molecular mechanism for Se uptake is still poorly understood. Herein, we show evidence that the uptake of selenite, a main bioavailable form of Se in paddy soils, is mediated by a silicon (Si) influx transporter Lsi1 (OsNIP2;1) in rice. Defect of OsNIP2;1 resulted in a significant decrease in the Se concentration of the shoots and xylem sap when selenite was given. However, there was no difference in the Se concentration between the wild-type rice and mutant of OsNIP2;1 when selenate was supplied. A short-term uptake experiment showed that selenite uptake greatly increased with decreasing pH in the external solution. Si as silicic acid did not inhibit the Se uptake from selenite in both rice and yeast (Saccharomyces cerevisiae) at low pHs. Expression of OsNIP2;1 in yeast enhanced the selenite uptake at pH 3.5 and 5.5 but not at pH 7.5. On the other hand, defect of Si efflux transporter Lsi2 did not affect the uptake of Se either from selenite or selenate. Taken together, our results indicate that Si influx transporter OsNIP2;1 is permeable to selenite.